Colombia : 2007 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
Colombia's economic performance has been strong, aided by sound economic policies. Structural reforms and prudent macroeconomic policy management has contributed to higher economic growth and lower inflation. Executive Directors commended the economic strategy, which has increased economic growth and international reserves and reduced unemployment and public debt ratio. Directors emphasized the need for tightening the monetary policy stance and a strong fiscal policy to achieve a 'soft landing' from economic boom.. They commended the countercyclical provisioning in the banking system, and emphasized the importance of a comprehensive tax reform.